Matematyka
TwojaHazexD
2017-06-22 22:08:09
Doprowac sume algebraiczną do najprostrzej postaci a) -(3x-2)+(x-1)= B) (3x2-5x+2)+(-2x2-x-3)- C) -(2ah-4a+3h)-(ab+7a-5h)=
Odpowiedź
kiniani
2017-06-22 23:19:15

a) -(3x-2)+(x-1)=-3x+2+x-1=-2x+1 b) (3x²-5x+2)+(-2x²-x-3)=3x²-5x+2-2x²-x-3=x²-6x-1 c) -(2ah-4a+3h)-(ab+7a-5h)=-2ah+4a-3h-ab-7a+5h=-2ah-3a-ab+2h

Konto usunięte
2017-06-22 23:20:30

a)  -(3x-2)+(x-1)=-3x+2+x-1=-2x+1 b)  (3x² -5x+2) +(-2x²  -x-3) =3x² -5x+2 - 2x²-x-3 =x² -6x -1 c)   -(2ah - 4a +3h)-(ab+7a-5h)=      -2ah+4a-3h-ab-7a+5h=     -2ah-3a+2h -ab

Dodaj swoją odpowiedź